The Influence of the Indonesian Realistic Mathematics Education Approach on the Ability to Understand Concepts and Mathematical Representation in Fractional Number Material - Hendri; Masrul; Kasman Ediputra (Institute of Educational, Research, and Community Service, 2024)
This study examines the effect of the Indonesian Realistic Mathematics Education (PMRI) approach on students' conceptual understanding and mathematical representation skills, especially in the context of fractions. This study was conducted at SD Negeri 26 Bantan, where students often show negative perceptions of mathematics, which causes difficulties in understanding and representing mathematical concepts. The PMRI approach, adapted from the Realistic Mathematics Education (RME) model developed in the Netherlands, emphasizes the use of real-world contexts and guided discovery to facilitate mathematical understanding. This study used a quasi-experimental design with a control group to compare the effectiveness of the PMRI approach with traditional teaching methods. The results showed that the PMRI approach significantly improved students' conceptual understanding and ability to represent mathematical ideas in various forms compared to conventional methods. These findings suggest that PMRI can be an effective strategy to improve mathematics learning outcomes, especially in the area of ​​fractions. This study contributes to the growing body of evidence supporting the use of realistic contexts in mathematics education to promote deeper understanding and student engagement.